Persepsi Kinerja dan Dampak Transportasi Online terhadap Pendapatan Pengemudi Angkutan Kota (Studi Kasus Trayek R.02 Kota Kendari) - Soeparyanto, Try Sugiyarto; Adiyaksa, Reza; Putra, Adris Ade; Statiswaty, Statiswaty (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Online-based transportation is rife amidst the condition of the public transportation system in urban areas and in the City of Kendari, Southeast Sulawesi, which needs to be better organized. Offering high flexibility and accessibility, affordable costs, multilevel comfort, and even security guaranteed by the company, it is undeniable that people who need to make a switch move under the pretext of consumer freedom to choose better. Social jealousy cannot be contained, especially for conventional transportation (Angkot) already operating. Gradually the number of online-based transport fleets is increasing, and of course, it affects the income of Angkot drivers. Therefore, reviewing the performance from the passengers' perspective tries to see to what extent the Angkot can meet expectations. The analysis used the Customer Satisfaction Index (CSI) method and Importance Performance Analysis (IPA). In addition, the statistic tests whether public transportation drivers have decreased income due to the increasing prevalence of online-based transportation. Respondents of public transportation passengers (users) were 400 people and 91 public transportation drivers. The results show that Online Transportation's presence hurts public transportation drivers' income levels. A decrease in the level of income of the drivers indicates this difference. The average daily income before online transportation was Rp. 151,000 - Rp. 200,000 and Rp. 51,000 - Rp. 100,000 after. On the other hand, for users, the results of the CSI analysis show that the Fare Variable is considered Satisfied for the user. At the same time, Safety, Comfort, Regularity, Smoothness, and Accuracy are rated Normal/Neutral. The Dissatisfied Variables are Safety and Pollution. In the IPA analysis, seven attributes are in Quadrant II, which means that users rate public transportation as 'Keep Up The Good Work', and six attributes are in Quadrant I, which means they need serious attention and 'improvement'. While the other 16 attributes are in quadrants III and IV, namely 'Low Priority' and 'Possible Overkill'.